2013
DOI: 10.1155/2013/135709
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Ontogenetic Variability in Plasma Composition of Juvenile and AdultBothrops jararacaSnakes

Abstract: The ontogenetic variability in venom composition of some snake genera, including Bothrops, as well as the biological implications of such variability and the search of new molecules that can neutralize the toxic components of these venoms have been the subject of many studies. Thus, considering the resistance of Bothrops jararaca to the toxic action of its own venom and the ontogenetic variability in venom composition described in this species, a comparative study of the plasma composition of juvenile and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
4
15
1
3
Order By: Relevance
“…Manuscript to be reviewed A previous study evaluating the ontogenetic changes in the plasma proteomic profile of B. jararaca snakes showed that BJ46a is present in a higher relative abundance in the plasma of adult specimens (de Morais-Zani et al 2013) suggesting a positive association with the higher hemorrhagic activity described in the venom of adult snakes (Antunes et al 2010). However, the results presented herein showed no significant differences in BJ46a-like transcript levels between juvenile and adult B. jararaca snakes.…”
Section: Plasma Protease C1 Inhibitormentioning
confidence: 61%
See 3 more Smart Citations
“…Manuscript to be reviewed A previous study evaluating the ontogenetic changes in the plasma proteomic profile of B. jararaca snakes showed that BJ46a is present in a higher relative abundance in the plasma of adult specimens (de Morais-Zani et al 2013) suggesting a positive association with the higher hemorrhagic activity described in the venom of adult snakes (Antunes et al 2010). However, the results presented herein showed no significant differences in BJ46a-like transcript levels between juvenile and adult B. jararaca snakes.…”
Section: Plasma Protease C1 Inhibitormentioning
confidence: 61%
“…qPCR results showed that the levels of transcripts encoding to γ-PLI was 30-fold higher in adult than those observed in juvenile specimens. At a first glance, these are unexpected results, since a previous plasma proteomic analysis indicated that γ-PLI are found in a higher relative abundance in the plasma of juvenile B. jararaca (de Morais-Zani et al 2013) and the venom of juvenile specimens also displayed higher catalytic PLA 2 activity (Antunes et al 2010). However, a study conducted by Kinkawa et al (2010) showed that the gene expression of α-, βand γ-PLIs was induced by the intramuscular injection of venom in the venomous snake Gloydius brevicaudus.…”
Section: Jararaca Nevertheless the Mechanisms Underlying The Regulamentioning
confidence: 84%
See 2 more Smart Citations
“…Some important elements which included to the composition of the snake venom are isolated for the medicinal purpose. The BJ46a compound which belongs to the composition of the snake venom has inhibition effect; it inhibits MMPs which is activated in cancer metastasis [15].…”
Section: Component Of Snake Venom (Bj46a) and Mmpsmentioning
confidence: 99%